Behavioral and cultural determinants of symptomatic dry eye disease among university students in the UAE - Mona Aridi; Nisreen Alwan; Wissam Ghach (PLoS ONE, 2026)
Objectives This study aims to estimate the prevalence of symptomatic Dry Eye Disease (DED) and its associated risk factors among university students in the UAE. Methods A cross-sectional study was conducted among 654 participants using the validated Ocular Surface Disease Index (OSDI) questionnaire, distributed via an online Google survey. The survey assessed the prevalence of DED along with demographic and behavioral-cultural risk factors. Kruskal-Wallis test was employed to analyze group differences. Spearman’s rank correlation evaluated associations between OSDI scores and quantitative variables. Results The study revealed significant gender differences, with females reporting higher OSDI scores than males. Smoking behaviors were strongly associated with OSDI scores, with daily smokers and those smoking in indoor environments. Among smoking types, Dokha and Mouassal waterpipe users exhibited the highest median OSDI scores. Eye cosmetic practices with users of shorter annual usage reported higher scores, while effective cleansing methods, such as soap and water or cleansing creams, were associated with lower scores. Prolonged screen time and extended study hours were positively correlated with OSDI scores. Conclusions Symptomatic DED is highly prevalent among UAE university students. These findings underscore the need for targeted awareness and prevention strategies to mitigate DED risk factors within this population.